CORRELATION BETWEEN SELF-ESTEEM AND STATE ANXIETY IN PROFESSIONAL SELF-DETERMINATION FORMATION - Dolgova Valentina Ivanovna,; Grasmik Elizaveta Aleksandrovna,; Nurtdinova Anna Alekseevna,; Gamova Elena Minnullovna, (Scientific Journal of Pedagogy and Economics, 2021)
The study focuses on professional self-determination formation in high school students as a correlation between their anxiety and self-esteem is considered to be highly important in the study of human resources. The purpose of the study is to determine on the basis of theoretical arguments a correlation between self-esteem and state anxiety in students in the process of professional self-determination and prove it with an experiment. The study was conducted in Kuzino State School 36 of the Sverdlovsk Region. The study was carried out in three stages: desktop analysis, experimental research, and data analysis. The research comprised empirical methods in the form of an ascertaining experiment and testing, statistical and mathematical methods in the form of Spearman's rank correlation coefficient, and three techniques: the Dembo-Rubinstein technique for self-esteem evaluation modified by A.M. Prikhozhan, the Kazantseva technique for general self-esteem assessment, and the State-Trait Anxiety Inventory, developed by C.D. Spielberger and modified by Yu.L. Khanin. The research on self-esteem of students in the process of professional self-determination showed the following findings. Based on the Dembo-Rubinstein technique, average self-esteem prevails among study subjects (67%); moreover, the Kazantseva technique demonstrated the prevalence of average self-esteem among high school students as well (63%). The State-Trait Anxiety Inventory also showed that most of the subjects (68%) had an average level of anxiety. In the study, experiments were performed and levels of self-esteem and state anxiety in professional self-determination formation were determined; a correlation between self-esteem and state anxiety was proven. Study findings demonstrated that most students had average self-esteem and average state anxiety. Thus, according to Spearman's rank correlation coefficient, there is indeed a correlation between self-esteem and state anxiety in students in the process of professional self-determination.